Single-nucleus transcriptomics reveals a distinct microglial state and increased MSR1-mediated phagocytosis as common features across dementia subtypes - Sook-Yoong Chia; Mengwei Li; Zhihong Li; Haitao Tu; Jolene Wei Ling Lee; Lifeng Qiu; Jingjing Ling; Richard Reynolds; Salvatore Albani; Eng-King Tan; Adeline Su Lyn Ng; Jinmiao Chen; et al. (Genome Medicine)
Abstract Background Alzheimer’s disease (AD), dementia with Lewy bodies (DLB), and Parkinson’s disease dementia (PDD) collectively represent the majority of dementia cases worldwide. While these subtypes share clinical, genetic, and pathological features, their transcriptomic similarities and differences remain poorly understood. Methods We applied single-nucleus RNA-sequencing (snRNA-seq) to prefrontal cortex samples from individuals with non-cognitive impairment control (NCI), and dementia subtypes (AD, DLB, and PDD) to investigate cell type-specific gene expression patterns and pathways underlying pathological similarities and differences across dementia subtypes. SnRNA-seq findings were validated through RNAscope, immunohistochemistry, and additional biochemical analyses in human tissues and cellular models. Results SnRNA-seq analysis revealed elevated microglial proportions across all dementia subtypes compared to NCI. Further analysis of cell type-specific transcriptomes identified overlapping differentially expressed genes (DEGs) between microglia and oligodendrocytes across all dementia subtypes. While AD showed molecular similarities to NCI, PDD and DLB were clustered more closely together, sharing a greater number of DEGs and related pathways, predominantly associated with microglia. Investigation of interactions between microglia and oligodendrocytes revealed a distinct microglial state in all dementia subtypes. MSR1, a gene encoding a scavenger receptor, was upregulated in microglia across all dementia subtypes, along with its associated gene HSPA1A in oligodendrocytes. RNAscope supported the potential interaction between microglia and oligodendrocytes, where these cells were in closer proximity to each other in human cortical tissues of PDD compared to NCI. MSR1 expression was significantly increased in cortical primary microglia from PD mice compared with non-transgenic (NTg) mice. Additionally, the expression of myelin-associated genes (MBP, MOBP, and PLP1) was significantly upregulated in PD microglia compared to NTg, supporting the presence of the distinct microglia. Furthermore, MSR1-positive microglia colocalised with MBP in cortical tissue of PDD patients, suggesting a functional role of MSR1 in myelin debris clearance. Overexpression of MSR1 in microglial cells enhanced their phagocytic activity toward myelin, and reciprocally, myelin treatment upregulated MSR1 protein levels, indicating enhanced MSR1-mediated myelin phagocytosis. Conclusions Our findings provide novel insights into the cell type-specific role of microglial MSR1 in AD, DLB, and PDD, linking its increased phagocytic capacity to myelin defects as a common feature of neurodegenerative dementias.